2014
DOI: 10.1038/nmat4145
|View full text |Cite
|
Sign up to set email alerts
|

Coherent control of single spins in silicon carbide at room temperature

Abstract: Spins in solids are cornerstone elements of quantum spintronics. Leading contenders such as defects in diamond or individual phosphorus dopants in silicon have shown spectacular progress, but either lack established nanotechnology or an efficient spin/photon interface. Silicon carbide (SiC) combines the strength of both systems: it has a large bandgap with deep defects and benefits from mature fabrication techniques. Here, we report the characterization of photoluminescence and optical spin polarization from s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
672
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 581 publications
(712 citation statements)
references
References 36 publications
34
672
1
5
Order By: Relevance
“…Using a solid immersion lens, a count rate of 4 Â 10 4 c.p.s. has been achieved 40 , supporting the conclusions drawn here.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Using a solid immersion lens, a count rate of 4 Â 10 4 c.p.s. has been achieved 40 , supporting the conclusions drawn here.…”
Section: Discussionsupporting
confidence: 89%
“…Note, when the manuscript was in the reviewing process, we learnt about two papers where the coherent control of single spins in SiC is reported 39,40 . Using a solid immersion lens, a count rate of 4 Â 10 4 c.p.s.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that this feedback-based protection algorithm can protect the qubit coherence far beyond the dephasing time of the qubit, even if no active control is applied to decouple it from the noise. The algorithm can be extended to applications in quantum information processing and quantum sensing, and it could be implemented in many other hybrid spin systems, such as phosphorus [27] or antimony [28] donors in silicon, defects in silicon carbide [29] or quantum dots [30]. As we applied a coherent feedback protocol, thus avoiding measuring the state of the ancilla, the decoherent effects of the bath are effectively stored in the ancilla.…”
Section: Figmentioning
confidence: 99%
“…It is both an industrially important substrate for high-performance electronic devices [1] and a host to several types of vacancy-related paramagnetic color centers with remarkable attributes . Much like the diamond nitrogen-vacancy center [24,25], these color centers have electronic spin states that can be addressed at either ensemble or single-spin levels [18,19] through optically detected magnetic resonance (ODMR). Moreover, spin coherence times can exceed 1 ms [18], and ODMR can persist up to room temperature [10,11,14,19].…”
mentioning
confidence: 99%
“…Much like the diamond nitrogen-vacancy center [24,25], these color centers have electronic spin states that can be addressed at either ensemble or single-spin levels [18,19] through optically detected magnetic resonance (ODMR). Moreover, spin coherence times can exceed 1 ms [18], and ODMR can persist up to room temperature [10,11,14,19]. Although the fluctuating nuclear spin bath is a principal source of electronic spin decoherence in these types of systems [26], nuclear spins in SiC are not purely detrimental.…”
mentioning
confidence: 99%